The Roles of Oxytocin and CD38 in Social or Parental Behaviors - Lopatina, Olga; Inzhutova, Alyona; Salmina, Alla B.; Higashida, Haruhiro (Frontiers in Neuroscience, 2013)
The nine amino acid peptide oxytocin (OXT) has been directly associated with different types of behavioral reactions. The formation and maintenance of social relationships in youth and middle age are important components of human mental health. A deficit in healthy behavioral formation leads to social isolation and limitation of well-being. Mice are social animals and are therefore useful for investigating the neurobiological mechanisms of cognitive process control, including the development of social relationships and social skills. Studies in mice may broaden our understanding of the human condition. The multifunctional protein CD38/ADP-ribosyl cyclase is highly expressed in the brain, plays an important role in central OXT release, and regulates social memory. In this review article, we discuss the mechanisms of social behavior affected by the dysregulation of brain OXT function as a consequence of a lack of CD38. OXT bound to OXT receptors initiates autoregulatory positive feedback of OXT release in the hypothalamus and posterior pituitary. OXT bio-behavioral positive feedback is usually implicated in female reproductive systems, but can also be observed in social behavior. Exogenous stimuli (OXT treatment in vitro, OXT intravenous or intraventricular administration, and nasal OXT delivery) initiate activation of OXT neurons via PKC-CD38/ADP-ribosyl cyclase cascades and result in the modulation of social behavior in humans and mice. Based on these findings, we reviewed the functions of OXT and its properties with respect to the development of therapies for human social behavior impairments in psychological diseases. In addition, preliminary studies of continuous nasal OXT administration on subjects with autism spectrum disorders are described.